Komentarz do Bibliografii przekładów literatury polskiej w Serbii w 2014 roku - Filipek, Małgorzata (Przekłady Literatur Słowiańskich, 2015)
Comments to the Polish‑Serbian bibliography in 2014 The text focuses on the translations of Polish literature. 27 Polish books of 16 authors were published in Serbia. Only 4 of them are volumes of poetry. Most of these translations appeared in Serbia earlier. Themes of Polish books coincides with themes of Serbian literature. Key words: Polish literature, Serbia, translations.